Sedimentary facies, stratigraphy, and depositional environments of the Ecca Group, Karoo Supergroup in the Eastern Cape Province of South Africa - Baiyegunhi, Christopher; Liu, Kuiwu (De Gruyter, 2021)
The stratigraphy of the Ecca Group has been subdivided into the Prince Albert, Whitehill, Collingham, Ripon, and Fort Brown Formations in the Eastern Cape Province, South Africa. In this article, we present detailed stratigraphic and facies analyses of borehole data and road-cut exposures of the Ecca Group along regional roads R67 (Ecca Pass), R344 (GrahamstownAdelaide), R350 (Kirkwood-Somerset East), and national roads N2 (Grahamstown-Peddie) and N10 (Paterson-Cookhouse). Facies analysis of the Ecca Group in the study area was performed to deduce their depositional environments. Based on the lithological and facies characteristics, the stratigraphy of the Prince Albert, Whitehill, Collingham, and Fort Brown Formations is now subdivided into two informal members each, while the Ripon Formation is subdivided into three members. A total of twelve lithofacies were identified in the Ecca Group and were further grouped into seven distinct facies associations (FAs), namely: Laminated to thin-bedded black-greyish shale and mudstones (FA 1); Laminated black-greyish shale and interbedded chert (FA 2); Mudstone rhythmite and thin beds of tuff alternation (FA 3); Thin to thick-bedded sandstone and mudstone intercalation (FA 4); Medium to thick-bedded dark-grey shale (FA 5); Alternated thin to medium-bedded sandstone and mudstone (FA 6); and Varved mudstone rhythmite and sandstone intercalation (FA 7). The FAs revealed gradually change of sea-level from deep marine (FA 1, FA 2, FA 3 and FA 4, FA 5, and FA 6) to prodelta environment (FA 7). This implies that the main Karoo Basin was gradually filling up with Ecca sediments, resulting in the gradual shallowing up of the water depth of the depositional basin.
Journal article published in the journal of Open Geosciences 2021; 13: 748–781
Keywords: Stratigraphy; Lithofacies; Depositional environment; Ecca Group; Karoo Supergroup; Groups (Stratigraphy) -- South Africa; Lithofacies; Facies (Geology); Ecca Group; Karoo Supergroup